Brand value dan nilai perusahaan di Indonesia - Fuad Husnul Yaqin; Prasetyono Prasetyono (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2021)
This study aims to prove the effect of brand value on firm value. The research sample is companies listed in the 100 Most Valuable Brands of Indonesia and the Indonesia Stock Exchange 2015-2019, totaling 250 with purposive sampling technique, while the data analysis technique uses multiple linear regression analysis. As a result, we get the first evidence that brand value and book value per share does not affect firm value. In addition, earnings per share and market capitalization also affect firm value. This result means that the investor's decision to buy shares is a strategic and long-term decision with consideration of its prospects in the future.